Gamification-based multimedia as a catalyst for character building in elementary school students - Miftahul Hikmah; Dedi Kuswandi; Candra Utama (University of Muhammadiyah Malang, 2026)
The phenomenon of declining responsibility among primary school students is a serious challenge, with conventional teaching methods deemed ineffective in fostering discipline and internal motivation in students on a sustainable basis. This situation creates an urgent need for pedagogical innovation that can bridge the gap between values education and the characteristics of the digital generation, making the integration of technology in learning an absolute necessity for optimising character internalisation. This study aims to develop a sense of responsibility in primary school students through a gamification-based multimedia approach in learning about ethnic diversity in East Java. A quantitative approach with a one-group pre-test post-test design was applied to 20 fourth-grade students at SDN Dadaprejo 02 Kota Batu, using a questionnaire as a data collection instrument with indicators of consistency, self-motivation, and discipline. Data analysis using a paired sample t-test and effect size calculation (Cohen's d) showed an increase in the average student responsibility score from 17.95 to 38.05, with a significance value of <0.001 and a Cohen's d value of 5.96, indicating the effectiveness of the treatment with a very strong category. The results of the discussion show that the multimedia gamification activity design succeeded in significantly improving the three indicators, as reflected in the increase in the total score from 359 to 761. This approach is effective in building students' responsibility character, as evidenced by the comprehensive and meaningful improvement in consistency, self-motivation, and discipline in learning.